Alepia viatrix sp. nov. (Diptera: Psychodidae), a new species of a Neotropical genus found on the Azores Archipelago (Portugal) - Jaume-Schinkel, Santiago; Kvifte, Gunnar Mikalsen; van Der Weele, Ruud; Mengual, Ximo (Zootaxa, 2022)
A new species of the Neotropical genus Alepia Enderlein, 1937 is described from the Azores Archipelago based on morphological characters and DNA barcodes from male and female specimens. Images of the new species as well as a discussion of the origin of this species are also provided. Moreover, we include an identification key for the adult male Psychodidae species recorded on the Azores Archipelago and comment on each species present on these islands. This is the first record of the genus Alepia from Azores.